Islamic Moderation in Poverty Alleviation Strategy: A Study of Ibn Khaldun’s Economic Thought - Hardiansyah Padli; Rahma Detik Kurningsih (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
Poverty remains an ongoing challenge in Indonesia despite relatively stable economic growth. This condition demonstrates the limitations of a technocratic approach to development, which often neglects ethical and social dimensions. This study aims to explore Ibn Khaldun's economic thinking as a basis for poverty alleviation within the framework of Islamic moderation (wasatiyyah). This study uses a qualitative approach based on literature review with thematic analysis of al-Muqaddimah and relevant contemporary literature in the field of Islamic economics. The results show that Ibn Khaldun's eight principles of development, particularly those related to the role of the state, institutions, human resource development, wealth distribution, and justice, reflect a moderate development model that integrates moral, spiritual, and economic dimensions. This model rejects extreme approaches such as minimalist or authoritarian states, and views wealth as a means of distributing social welfare, not as a tool for accumulating power. This study concludes that Ibn Khaldun's framework of thought provides a coherent epistemic foundation for inclusive and equitable development, and remains relevant to the contemporary Indonesian context. The scientific contribution of this research lies in its synthesis of classical Islamic development theory and the principles of Islamic moderation, thereby offering an alternative to conventional economic paradigms that tend to marginalize moral and social dimensions.